Erosion, reform and viability of the Monarchy - Fraguas de Pablo, Rafael (Razón y fe, 2022)
The image of the previous holder of the Crown and its projection on the image of the Monarchy as an institution have been and are a cause of social and political concern in Spain since some years before the abdication of its holder, Juan Carlos I, in June 2014. Such concern has obeyed — and continues to obey — to intermittent informative revelations about certain irregular economic-financial and fiscal practices attributed to him or to his immediate environment, family included, from different judicial instances. A reform of the functions of the monarchy by means of a Statute that rationalizes its attributions and prevents the transgression of its prerogatives could be an exemplary starting point that would require, however, a parliamentary majority.